Phase Change Material for Thermal Comfort Improvement in Tropical Climate of Cameroon - Ekoe, A. A. M.; Mackpayen, Auguste Oscar; Kennedy, Nembot Ouembe; Robert, Mbiake (European Journal of Applied Sciences, 2024)
Current typical dwellings in the Sub-Saharan tropical climate of Cameroon provide opportunities for more effective design and the use of Phase-change materials (PCM) to reduce cooling energy demand. In this paper, a typical residential house of a single family is modelled with the local construction habits and materials under the tropical region of Cameroon. Energy analysis of the building is performed, taking into account the use of PCM paraffin RT26 in order to enhance the thermal comfort of the building. The impact of using phase change material on indoor air temperature is quantified. The results of the numerical analysis obtained show that the PCM can be a good option in a hot climate for reducing indoor air temperature. The average annual indoor air temperature was reduced from 35°C to 25°C.